Interest, reserves, and prices - Gianluca Benigno; Pierpaolo Benigno (Federal Reserve Bank of New York, 2021)
We would like to propose a new framework for monetary policy analysis that encompasses, as a special case, the Neo-Wicksellian paradigm. A general form of an aggregate-demand equation reveals a role for liquidity, as well as less effective movements in future real rates with respect to current ones, in stimulating aggregate demand. The quantity of reserves and their interest rate both matter for determining inflation and economic activity.
Keywords: E31; E43; E52; E58; 330; monetary policy framework; reserves; inflation